IPTEKS ANALISIS SWOT TENTANG PERKEMBANGAN PASAR PINASUNGKULAN SAGERAT - Moray, Christian Morgan; Rondonuwu, Sintje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Swot analysis is a problem solving process in determining the best strategy for the progress of the organization by looking at aspects of strengths, weaknesses, opportunities and threats. Swot analysis is accompanied by looking at the efas ifas and swot matrix for measuring the strategy assessment that will be taken. SWOT analysis process by identifying internal factors and external factors by means of data collection and field surveys aimed at obtaining aspects in internal factors and external factors. aspects of strengths and weaknesses are internal because they start from within the organization itself, while aspects of opportunities and threats are included in the external because they originate outside the organization, then the process is continued by connecting internal and external factors in the SWOT matrix to get four strategies, namely how to exploit opportunities, how weaknesses take advantage of opportunities, how strengths minimize threats and how weaknesses and threats seek solutions. from these results can be reflected which strategy is the best to run.Keywords : Strategic planning ,evaluate strenghs, evaluate weaknesses, evaluate opportunities, evaluate threats